Convolution of Hankel transform and its application to an integral involving Bessel functions of first kind - Vu Kim Tuan; Megumi Saigo (International Journal of Mathematics and Mathematical Sciences, 1995)
In the paper a convolution of the Hankel transform is constructed. The convolution is used to the calculation of an integral containing Bessel functions of the first kind.